-5x-7=9x+15

Simple and best practice solution for -5x-7=9x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-7=9x+15 equation:


Simplifying
-5x + -7 = 9x + 15

Reorder the terms:
-7 + -5x = 9x + 15

Reorder the terms:
-7 + -5x = 15 + 9x

Solving
-7 + -5x = 15 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-7 + -5x + -9x = 15 + 9x + -9x

Combine like terms: -5x + -9x = -14x
-7 + -14x = 15 + 9x + -9x

Combine like terms: 9x + -9x = 0
-7 + -14x = 15 + 0
-7 + -14x = 15

Add '7' to each side of the equation.
-7 + 7 + -14x = 15 + 7

Combine like terms: -7 + 7 = 0
0 + -14x = 15 + 7
-14x = 15 + 7

Combine like terms: 15 + 7 = 22
-14x = 22

Divide each side by '-14'.
x = -1.571428571

Simplifying
x = -1.571428571

See similar equations:

| -7-8n=47 | | 5=18 | | 3(-x)+5x=x+9 | | 2(-x)+5x=x+9 | | .1x=-13 | | (12x-30)+3x=180 | | -65-12x+8x=55 | | 2x+3x-40=50 | | ab+bc+ac=-abc | | -19-2x+4x=7 | | 5X-(3)+(-9)=4x-(-7+1) | | ab+bc+ac=1110 | | 2(x+4)+4x-x=2x+20 | | -26-5b=4-7b | | 7+9-3b+20= | | 16-2x=4x | | 6r^2+8r-20=5r^2 | | -91+x+8x=35 | | 2m^2+2m-12=12 | | x=4x+39 | | 9x-76-4x=39 | | 7x-24-9x=10 | | 7x^18/21x^6 | | -19+6x-4x=5 | | 3/x-4/x-3=5 | | 5x^8+39x^4-8=0 | | 7x-23-3x=29 | | -2x-10+x=15 | | Y=-4x+6Y=5x-21 | | -83-9x+x=101 | | (12k^4)+(5k^2)-2=0 | | X+13x+40=0 |

Equations solver categories